Revealing the dynamics of magnetosphere, atmosphere, and interior of solar system objects with the Square Kilometre Array. (14th October 2022) - Kimura, Tomoki; Fujii, Yuka; Kita, Hajime; Tsuchiya, Fuminori; Sagawa, Hideo; ,
Abstract: Bodies such as planets, moons, and asteroids in our solar system are the brightest objects in the low-frequency radio astronomy at ≲10 GHz. The low-frequency radio emissions from our solar system bodies exhibit various observed characteristics in the spectrum, polarization, periodicity, and flux. The observed characteristics are essential probes for explorations of the bodies' magnetosphere, atmosphere, surface, and even their interior. Generation and propagation theories of the radio emissions associate the characteristics with fundamental physics embedded in the environments: e.g., auroral electron acceleration, betatron acceleration, and atmospheric momentum transfer. Here we review previous studies on the low-frequency radio emissions from our solar system bodies to unveil some outstanding key questions on the dynamics and evolution of the bodies. To address the key questions by the future observations with the Square Kilometre Array (SKA), we made feasibility studies for detection and imaging of the radio emissions. Possible extensions of the solar system observations with SKA to the exoplanets are also proposed in the summary.